Quality Control of Herbal Drug (Paxherbal Bitter Tea) Via Thin-Layer Chromatography and Phytoconstituent Analysis (Sciences of Pharmacy, 2023)
The effectiveness of any herbal medication depends on the presence or absence of pharmacologically active phytocompounds. These ingredients are significantly affected by the quality control system espoused during and after manufacturing processes and the operation of such pharmaceuticals. Thin-layer chromatography (TLC) is a quality control parameter suitable to identify and codify substances predicated on their distinctiveness and uniformity, giving an identity for such substances. Paxherbal Bitter Tea is a polyherbal medicine harnessed as an anti-diabetes medicine. This study assessed the distinguishable phytoconstituents present and evolved attribute profiles (TLC) for the herbal (Paxherbal Bitter Tea) to serve as a quality control check during manufacturing for consistency and market identity. Qualitative phytochemical and chromatographic assays were carried out employing standard methodologies. The qualitative test revealed the presence of saponin, steroids, reducing sugar, cardiac glycoside, and terpenoids, and the finger-print chromatograms after progression with n-hexane: ethyl acetate (9:1) flaunted three dissimilar elements under ultraviolet light at 365 nm and five spots, when dotted with 20% methanolic sulphuric acid under visible light. In this study, we developed an identity profile for Paxherbal Bitter Tea via its unique chemical biographies, which can be exercised in verifying the quality and consistency of the herbal product.